Almost all Steiner triple systems are almost resolvable. (3rd November 2020) - Ferber, Asaf; Kwan, Matthew
Abstract: We show that for any n divisible by 3, almost all order- n Steiner triple systems admit a decomposition of almost all their triples into disjoint perfect matchings (that is, almost all Steiner triple systems are almost resolvable ).